Extramedular plasmocytoma of the rhinopharynx with subsequent dissemination to pancreas head and dorsal meninges.: A propósito de 1 observación - Piacenza, Guillermo; Priario, Julio C; Pizzarrosa, Carlos; Purriel, Juan; Vercelli, Jorge (Cirugía del Uruguay, 1985)
Communication of observation o( an extramedular plasmocytoma, with initial rhinopharyngeal location, later on extended to !he pancreas head and the dorsal dura mater after 20 and 26 months respectively after the initial diagnosis. The palien! is alive after 6 years of combined therapy. The caracterislics of this type of tu• mor are discussed with respect to bibliographic findings.